Pregnancy Complication Due to Malaria in Mice BALB/C : The Role of TNF-α, Anemia, and Low Birth Weight - Milliana, Alvi; Indriana, Nurfianti; Rahmah, Zainabur (Journal of Islamic Medicine, 2023)
Background : Malaria infection in pregnant women or called placental malaria is characterized by the accumulation of Plasmodium-infected red blood cells in the intervillous space of the placenta. This causes adverse perinatal outcomes such as stillbirth, low birth weight, premature birth, and small neonates of gestational age while in the mother it causes anemia. Inflammatory responses such as TNF-α expression can promote complications in pregnancy. TNF-α plays an important role in the immune response in acute malaria but inhibits erythropoiesis. Objective : This study aims to determine the relationship between malaria infection and TNF-α expression with the incidence of anemia and birth weight in pregnant mice infected with Plasmodium berghei. Methods: Twenty BALB/C pregnant mice were divided into 2 groups, control group (10 pregnant mice without infection) treatment group (10 pregnant mice infected with Plasmodium berghei). TNF-α expression was observed by immunohistochemical method using anti-TNF-α Chip Grade antibody from abcam, anemia examination using Cyanmethemoglobin and all fetuses were weighed using an analytical balance. Statistical analysis using Structural Equation Modeling. Results: Malaria infection causes high expression of TNF-α in the placenta (tcount=2.97≥ ttable = 1.96), causes anemia (tcount=1,97≥ttable = 1.96) and causes low fetal weight tcount=2,16 ≥ ttable =1, 96. Conclusion: Malaria infection can cause high expression of TNF-α in the placenta causing anemia and low birth weight of the fetus